2016
DOI: 10.21699/jns.v5i4.422
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Atresia: Association with Other Anomalies

Abstract: Background: Colonic atresia (CA) is a rare form of congenital intestinal atresia. Although CA may be isolated, it is more commonly reported in literature in association with other congenital anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 26 publications
1
25
0
2
Order By: Relevance
“…CA may be an isolated anomaly or associated with other congenital anomalies association with malrotation, anorectal malformation, gastroschisis, HD, limb malformation, and choledochal cyst has been reported. [ 1 2 3 4 5 14 15 16 19 ] In our study, we found association with malrotation in 3 cases, HD in 2 cases, unilateral cleft lip in 1, and cardiac anomaly 2 patient and Meckels diverticulum in 1 patient. Presence of anomalies alters overall mortality.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…CA may be an isolated anomaly or associated with other congenital anomalies association with malrotation, anorectal malformation, gastroschisis, HD, limb malformation, and choledochal cyst has been reported. [ 1 2 3 4 5 14 15 16 19 ] In our study, we found association with malrotation in 3 cases, HD in 2 cases, unilateral cleft lip in 1, and cardiac anomaly 2 patient and Meckels diverticulum in 1 patient. Presence of anomalies alters overall mortality.…”
Section: Discussionsupporting
confidence: 59%
“…Primary colo-colic anastomosis for atresia in the right colon and diverting colostomy for the left colon has been suggested by many studies earlier. [ 1 3 4 5 16 17 18 19 20 21 22 23 24 ] Dalla Vecchia et al . reported null mortality in 21 CA and in 3 out of 21 with primary one-stage anastomosis approach to CA.…”
Section: Discussionmentioning
confidence: 99%
“…The most common of the combined malformation is gastroschisis. Intestinal malrotation is less common as the combined malformation [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of colonic atresia is estimated at 1 in 20,000 (Mirza, Iqbal, & Ijaz, ) to 1 in 66,000 live births (Davenport, Bianchi, Doig, & Gough, ). Approximately one‐half of children with colonic atresia have additional defects (El‐Asmar, Abdel‐Latif, El‐Kassaby, Soliman, & El‐Behery, ; Etensel et al, ). If isolated colonic atresia is identified and treated early, the prognosis is good with an overall mortality of <26%; however, mortality increases considerably if there is a delay in treatment beyond 3 days (Etensel et al, ).…”
Section: Methods Optimizationmentioning
confidence: 99%